2012
DOI: 10.4081/ni.2012.e16
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between early and late stages of information processing: an event-related potential study

Abstract: The brain is capable of elaborating and executing different stages of information processing. However, exactly how these stages are processed in the brain remains largely unknown. This study aimed to analyze the possible correlation between early and late stages of information processing by assessing the latency to, and amplitude of, early and late event-related potential (ERP) components, including P200, N200, premotor potential (PMP) and P300, in healthy participants in the context of a visual oddball paradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 31 publications
4
15
0
Order By: Relevance
“…In both cases, the ERP components reflect the encoding, maintenance and recognition of the working memory items. The topographic posterior components of ERP (P2) reflect the sensory early stages of process, and the medium and late stages, representing the anterior topographic ERP components (N2 and P3) indicate the recognition and closure of the process [40]. In the more recent investigation that the authors of this research article are aware of, Kessler & coworkers [24], have reported the effect of updating memoranda over the ERP components.…”
Section: Event Related Potentials In the Study Of Vwmmentioning
confidence: 70%
“…In both cases, the ERP components reflect the encoding, maintenance and recognition of the working memory items. The topographic posterior components of ERP (P2) reflect the sensory early stages of process, and the medium and late stages, representing the anterior topographic ERP components (N2 and P3) indicate the recognition and closure of the process [40]. In the more recent investigation that the authors of this research article are aware of, Kessler & coworkers [24], have reported the effect of updating memoranda over the ERP components.…”
Section: Event Related Potentials In the Study Of Vwmmentioning
confidence: 70%
“…The P200 and N200 are understood to reflect basic sensory processing—termed lower-level processing—of the stimulus. The P200 is modulated by stimulus characteristics and by cognitive and task demands, and is generated in associative auditory temporal regions (Portella et al, 2012, Ferreira-Santos et al, 2012). The N200 is associated with discrimination and classification of the stimulus (Portella et al, 2012, Sumich et al, 2008) and has multiple subcomponents, with different generators (Patel and Azzam, 2005).…”
Section: Source Of Funding and Conflicts Of Interestmentioning
confidence: 99%
“…The P200 is modulated by stimulus characteristics and by cognitive and task demands, and is generated in associative auditory temporal regions (Portella et al, 2012, Ferreira-Santos et al, 2012). The N200 is associated with discrimination and classification of the stimulus (Portella et al, 2012, Sumich et al, 2008) and has multiple subcomponents, with different generators (Patel and Azzam, 2005). The P300 is made of two separate wave forms, the P3a and P3b, whose activity reflects coordinated activities in the prefrontal and posterior cortical areas during attention switching and updating of task sets in working memory (Meares et al, 2005).…”
Section: Source Of Funding and Conflicts Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…The P300 typically peaks around 300 ms post-stimulus at centro-parietal electrodes with neural generators in temporal and parietal regions (Polich, 2007; Dong et al, 2015), consistent with the timing and location of our source locations. This component has been associated with working memory and attentional processing (Patel and Azzam, 2005; Polich, 2007; Portella et al, 2012), and greater P300 amplitudes have been found to correlate positively with working memory capacity (Dong et al, 2015). Interestingly, this finding suggests that regardless of group membership (i.e., expert or control), participants with greater anagramming scores may have greater long-term working memory capacity in the SDT, as evident by greater P300 amplitudes in the right medial temporal lobe.…”
Section: Discussionmentioning
confidence: 99%